OPTIMASI KONDISI SINTESIS NANOPARTIKEL TEMBAGA MENGGUNAKAN EKSTRAK BIJI MELINJO (Gnetum gnemon L.) - Hilda Aprilia Wisnuwardhani; Arinda Roosma; Yani Lukmayani; Anggi Arumsari; Sukanta Sukanta (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Copper nanoparticles (CuNPs) is one of metal nanoparticles, which have many benefits especially in medicinal science. The aim of this research is to determine CuNPs synthesis optimum condition using melinjo seed extract as a bioreductor. In this work, copper (II) sulphate pentahydrate is used as a precursor. Melinjo seed extract was prepared at 600C using aquadest as a solvent. Two stabilizers were used i.e. Î²-cyclodextrin (BCD) and citric acid. The result showed that the optimum ratio condition of CuNPs synthesis is extract: CuSO4 1 mM: Î²-cyclodextrin 10 mg/mL = 1:1:1 (v/v/v). The CuNPs were synthesized by reflux method at 900C for 4 hours. It was observed that the addition of sonication process for 2 hours affected the stabilization of CuNPs. The average size of particles is 364,1 nm in diameter and 0,296 in polydispersity index.